Children's dimensions of poverty: Qualitative studies in urban China - Yang, L; Walker, RL; Zhang, G (Wiley, 2022)
The dimensionality of child poverty is not well understood because children are seldom asked systematically to describe their poverty experience. This hinders the prediction of poverty's long-term consequences and constrains policy design. In this research, 55 children aged 8–12 from Hangzhou and Beijing China were each interviewed individually for 0.5–2 h and participated in 3–4 focus group sessions on poverty experience. Integrating their understanding with the perspectives of parents and teachers suggests nine dimensions of poverty: four structural (material deprivation, limiting home environment, constrained education, restricted opportunities); three relational (violence, negative social relations, lack of confidence) and two core (shame, neglected agency).